Conversion of a telomere resolvase into a Cre-like site-specific recombinase - Shu Hui Huang; Mahrokh Balouchi; Kerri Kobryn (PLoS ONE, 2025)
Hairpin telomere resolvases are a unique family of enzymes involved in producing the hairpin (hp) telomeres of bacterial organisms and phages that possess linear DNA’s terminated by hp telomeres. The hp telomeres help to overcome the end-replication problem faced by linear DNAs and are generated from replicated intermediates of the linear DNAs. The telomere resolvases employ a reaction mechanism and catalytic domain related to that of the type IB topoisomerases and tyrosine recombinases. ResT, the telomere resolvase from Borrelia burgdorferi, under certain reaction conditions, has been shown to promote site-specific recombination between replicated telomere junctions (rTels) to produce a Holliday junction intermediate in a reaction strikingly similar to that promoted by tyrosine recombinases. TelA, the telomere resolvase of Agrobacterium tumefaciens, has been shown to be autoinhibited in such a manner as to forbid recombination between rTels. Relief of such autoinhibition reveals a weak, cryptic recombination activity in TelA. In the present study we characterize a catalytic domain aspartic acid residue mutation (D398A) that produces an enzyme with compromised telomere resolution activity but a massively stimulated ability to promote recombination between replicated telomere junctions to produce both the Holliday junction intermediate and full recombinant products of site-specific recombination between rTels. We also report that combination of the D398A mutation with previously characterized hyperactivating mutations in TelA produced a complete conversion of a telomere resolvase into a site-specific recombinase. The possible utility of this conversion is explored.